Universal recommendations for the management of acute diarrhea in nonmalnourished children - Guarino, A; Lo Vecchio, A; Dias, J; Berkley, J; Boey, C; Bruzzese, D; Cohen, M; Cruchet, S; Liguoro, I; Salazar-Lindo, E; Sandhu, B; Sherman, P; et al. (Lippincott, Williams and Wilkins, 2018)
Objective: Despite a substantial consistency in recommendations for the management of children with acute gastroenteritis (AGE), a high variability in clinical practice and a high rate of inappropriate medical interventions persist in both developing and developed countries. The aim of this study was to develop a set of clinical recommendations for the management of nonseverely malnourished children with AGE to be applied worldwide. Methods: The Federation of International Societies of Pediatric Gastroenterology, Hepatology, and Nutrition (FISPGHAN) Working Group (WG) selected care protocols on the management of acute diarrhea in infants and children aged between 1 month and 18 years. The WG used a 3-step approach consisting of: systematic review and comparison of published guidelines, agreement on draft recommendations using Delphi methodology, and external peer-review and validation of recommendations. Results: A core of recommendations including definition, diagnosis, nutritional management, and active treatment of AGE was developed with an overall agreement of 91% (range 80%–96%). A total of 28 world experts in pediatric gastroenterology and emergency medicine successively validated the set of 23 recommendations with an agreement of 87% (range 83%–95%). Recommendations on the use of antidiarrheal drugs and antiemetics received the lowest level of agreement and need to be tailored at local level. Oral rehydration and probiotics were the only treatments recommended. Conclusions: Universal recommendations to assist health care practitioners in managing children with AGE may improve practitioners’ compliance with guidelines, reduce inappropriate interventions, and significantly impact clinical outcome and health care-associated costs.